2008
DOI: 10.2147/ijn.s4399
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nanophase titania topography on bacterial attachment and metabolism

Abstract: Surfaces with nanophase compared to conventional (or nanometer smooth) topographies are known to have different properties of area, charge, and reactivity. Previously published research indicates that the attachment of certain bacteria (such as Pseudomonas fl uorescens 5RL) is higher on surfaces with nanophase compared to conventional topographies, however, their effect on bacterial metabolism is unclear. Results presented here show that the adhesion of Pseudomonas fl uorescens 5RL and Pseudomonas putida TVA8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Oscarpoly in the field. This results were supported by the findings of Palmqvist et al (2015), they found that TiO 2 NPs protected oilseed rape against A. brassicae infection and caused plant growth promoting of roots and increasing of adhesive force between B. amyloliquefaciens and plants by formation protective encapsulating interspecies (Chowdhury et al 2012;Webster et al 2008).…”
Section: -Effect Of Nanoparticls Of Cercospora Leaf Spot Diseasesupporting
confidence: 60%
See 1 more Smart Citation
“…Oscarpoly in the field. This results were supported by the findings of Palmqvist et al (2015), they found that TiO 2 NPs protected oilseed rape against A. brassicae infection and caused plant growth promoting of roots and increasing of adhesive force between B. amyloliquefaciens and plants by formation protective encapsulating interspecies (Chowdhury et al 2012;Webster et al 2008).…”
Section: -Effect Of Nanoparticls Of Cercospora Leaf Spot Diseasesupporting
confidence: 60%
“…TiO 2 NPs have become one of the most important substances in nanotechnology which caused plant growth promoting to roots of oilseed rape and protected the plants against Alternaria brassicae infection and adhesive effects on bacteria (Bacillus amyloliquefaciens; Palmqvist et al 2015). TiO 2 NPs is useful as protective encapsulating agents that increase adhesive force in the interspecies relation between bacteria and plants (Chowdhury et al 2012;Webster et al 2008). Ruffolo et al (2010) and Song et al (2014) found that ZnTiO 3 and Zn hydroxide carbonate NPs showed higher growth inhibition efficiency of A. niger and fungal activity against cotton Verticillium, Rhizopus, Mucorales than ZnONPs, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…For much smaller nanostructures, the reported effects differ strongly between being high and low adhesive [243,244]. It has been shown that even the smallest differences in surface nanoroughness can strongly affect microbial cells' attachment [245][246][247][248][249][250]. These variations must be connected with certain spacings of bacterial adhesion sites on the membrane or cell appendages, but there is no direct evidence in the literature so far.…”
Section: Surface Structurementioning
confidence: 99%
“…But the topographic characteristics of the surfaces are also expected to affect the adhesion process. This aspect has been considered and carefully studied [65][66][67] Some authors have reported an increase in bacteria adhesion with surface roughness [68,69] while others, the reverse effect [70,71]. In these studies the roughness is estimated with the root mean square of heights (Rq) that can be appropriate for certain surfaces.…”
Section: Accepted Manuscriptmentioning
confidence: 99%